1995
DOI: 10.1111/j.1365-2141.1995.tb08356.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell‐depleted allogeneic bone marrow transplantation for acute leukaemia using Campath‐1 antibodies and post‐transplant administration of donor's peripheral blood lymphocytes for prevention of relapse

Abstract: One hundred and forty-six patients with acute leukaemia (81 with ANLL and 65 with ALL) received allogeneic bone marrow transplantation from their fully matched siblings. 121 patients underwent T-cell depletion (TCD) using Campath 1 monoclonal rat anti-human lymphocyte (CDw52) antibodies; 67 with Campath 1M and 54 with Campath 1G isotypes. Patients were conditioned for transplant using either total body irradiation combined with chemotherapy (125 patients) or busulfan and cyclophosphamide (21 patients). 112 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(76 citation statements)
references
References 41 publications
7
68
1
Order By: Relevance
“…The reemergence of T cell depletion of BM grafts to prevent GVHD coupled with the use of DLI to treat minimal residual disease or the genetic manipulation of T lymphocytes with suicide genes which potentially enable the T cell response to be switched off when a detrimental GVHD reaction develops, are some of the novel approaches now reaching clinical application. 22,23 The monitoring of T cell chimaerism as an early marker for response using STR-PCR should be of benefit in monitoring new DLI therapy protocols, particularly in dose escalation studies for the treatment of molecular or cytogenetic relapse, where an early response indicator may eliminate the need for further infusions of T cells. The detailed monitoring of these new immunotherapeutic approaches at the molecular level should also increase the understanding of the effectors, mechanism and the kinetics of the GVL reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The reemergence of T cell depletion of BM grafts to prevent GVHD coupled with the use of DLI to treat minimal residual disease or the genetic manipulation of T lymphocytes with suicide genes which potentially enable the T cell response to be switched off when a detrimental GVHD reaction develops, are some of the novel approaches now reaching clinical application. 22,23 The monitoring of T cell chimaerism as an early marker for response using STR-PCR should be of benefit in monitoring new DLI therapy protocols, particularly in dose escalation studies for the treatment of molecular or cytogenetic relapse, where an early response indicator may eliminate the need for further infusions of T cells. The detailed monitoring of these new immunotherapeutic approaches at the molecular level should also increase the understanding of the effectors, mechanism and the kinetics of the GVL reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Graft failure occurred in 2-20% of HLA-identical T-cell-depleted sibling transplants compared to 0-2% of recipients of HLA-identical unmanipulated bone marrow (Champlin, 1993;Goldman et al, 1988;Maraninchi et al, 1987;Martelli & Aversa, 1993;Martin et al, 1985;Mitsuyasu et al, 1986;Naparstek et al, 1995;O'Reilly, 1992). In the present study graft failure occurred in 5% of cases which is less than previously reported in recipients of T-cell-depleted grafts Champlin, 1993;Kernan et al, 1989;O'Reilly, 1992;Patterson et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In general, T-cell depletion significantly reduces LFS after BMT and this is caused by higher relapse rates. LFS after T-cell-depleted BMT for leukaemia in CR1 or CP1 varied from 48% at 2 years to 25% at 7 years (Blaise et al, 1993;Marmont et al, 1991;Naparstek et al, 1995). In standard-risk recipients of HLA-identical unmanipulated grafts, LFS varied from 70% at 2 years to 40% at 10 years (Blaise et al, 1993;Chao & Blume, 1990;Chao et al, 1991;Clift et al, 1993;Goldman et al, 1988;Gratwohl et al, 1993;Marmont et al, 1991;Zhang et al, 1995;Zittoun et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the number of cells infused between patients who received BM and the single patient who received PBSC (data not shown). 14 All patients received cyclosporin (3 mg/kg/day) i.v. from day Ϫ1 to day +100.…”
Section: Pre-transplant Protocol and Bmtmentioning
confidence: 99%
“…[12][13][14] This is an attractive approach, especially for diseases in which the stem cells are relatively resistant, [15][16][17] the aim being to attempt to reduce post-BMT disease recurrence with no risk of GVHD, and to avoid total body irradiation in the preparatory regimen as far as possible because of its hazardous after-effects which include growth retardation and increased likelihood of secondary malignancies. 18,19 Our attempt towards achieving more effective eradication of the patient's stem cells and reducing disease recurrence without increasing regimen-related toxicity (RRT) consisted of T cell-depleted allogeneic BMT preceded by the classical preparative protocol of busulfan (BU)-cyclophosphamide (CY) which we intensified by the addition of thiotepa (TTP).…”
mentioning
confidence: 99%